Legal Status of AI-Generated Logos/Brands in Indonesian Intellectual Property Law - Timothius Richard Yudha Saputra; Diding Rahmat; Lenny Nadriana; Rizky Pratama (Green Publisher, 2026)
Artificial Intelligence (AI) has significantly transformed creative industries by enabling machines to generate aristic works such as images, designs, and logos used in commercial activities. The increasing use of AI-generated content raise important legal questions concerning authorship, ownership, and legal protection under intellectual property law. This study aims to analyze the legal status of AI-generated logos within the Indonesian intellectual property framework and to identify the most appropiate legal mechanism for protecting such works. This research applies a normative legal research method using statutory, conceptual, and comparative approach. The study examines Indonesian copyright law under Law No. 28 Of 2014 Concerning Copyright and Trademark Protection under Law No. 20 Of 2016 Concerning Trademarks and Geographical Indications. The results indicate that Indonesia copyright law remain human-centered, meaning that works generated autonomously by artificial intelligence do not fully meet the legal requierements for copyright law. However, AI-generated logos may still obtain legal protection through trademark registration under the first-to-file principle. This study concludes that trademark law currently provides the most effective legal mechanism for protecting AI-generated logos in Indonesia. The research also highlights the need for future legal reform to address the growing role of artificial intelligence in creative industries.